Cybercrime Personal Data Leakage - Salam, Muhamad Darus; Santoso, Aris Agus; Arum, Rina; Guantara, Peter (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This research aims to identify the forms of internet fraud practices through social media and networks as a form of cybercrime and to understand the prevention efforts against internet fraud practices through networks and social media as a form of cybercrime from the perspective of international law and electronic information technology laws. This research was conducted in the Cyber Security Team Section of PT. Cipta Raya Data Makmur in the Bogor area. The research method used in data collection is through literature research. Secondary data from literature and books related to the issues being studied by the author. The obtained secondary data is analyzed qualitatively. The results obtained from the research are as follows: 1) Web Fishing is an attempt to exploit fake websites to deceive potential victims; fishing websites will look similar to official websites and use domain names that are almost identical. This is called domain spoofing. 2) Internet fraud is regulated under international criminal law provisions and existing international cybercrime regulations. 3) International legal efforts and electronic information technology (ITE) laws in preventing internet fraud practices are made through the establishment of legal rules regarding cybercrime, both multilaterally and regionally.